Development Of Human Personalityperfection Reflected In Charles Dickens's A Christmas Carol Novel (1843): A Psychoanalytic Approach. - Supadmi,, Sri; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
The major problem in this study is to show the development of human personality-perfection in Charles Dickens's A Christmas Carol novel by using Psychoanalytic approach. In this research, the researcher uses qualitative research. The data of this study is from primary data source and secondary data source. The primary data source is A Christmas Carol novel while the secondary data sources are literary books, the author's biography, and the other relevant information. The data collection is collected from library research and the technique of the data is analyzed by descriptive analysis. The result of this study shows the following findings. First, from the structural analysis, it shows that Charles Dickens wants to convey the message how the human personality is subordinated by money and how they develop their personality from the error ways to be better. Second, based on Psychoanalytic analysis, Charles Dickens wants to convey the psychological phenomenon that tends to lead and give the development of human personality transformation in A Christmas Carol novel. He creates someone's heart awareness where the person can change his personality and gives the best selection.